Refugees as humanitarian actors: Explaining the creation of organisations led by displaced and stateless persons in Europe - Lorenzo Piccoli; Eréndira León-Salvador; Tae Kyeong Meixner-Yun; Daniela Movileanu; Ahmad Wali Ahmad Yar (European University Institute, Robert Schuman Centre for Advanced Studies, Migration Policy Centre, 2025)
This study presents an original mapping of organisations led by forcibly displaced and stateless persons (DSP) in Europe. Based on a multilingual survey of 100 organisations conducted between December 2024 and March 2025, it provides an overview of their goals, activities, and challenges, highlighting their critical role in humanitarian action, advocacy, and social cohesion. The mapping reveals a dynamic of crisis-driven formation: DSP-led organisations often emerge during acute displacement events, filling gaps in humanitarian assistance and advocacy. This also reveals a potential fragility: organisations created in response to emergencies face sustainability challenges, raising questions about their longevity and capacity to institutionalise beyond the immediate crisis. Those that do manage to institutionalise, demonstrate remarkable resilience, often sustaining activities through innovative resource mobilisation, strong community networks, and partnerships with other civil society actors. Most of these organisations operate with limited resources at the local level and prioritise meeting urgent needs such as housing, legal assistance, and social support, while challenging narratives that portray refugees as passive recipients of aid. Recognising and supporting this agency through targeted funding, capacity-building, and formal inclusion in policy processes is essential to strengthen humanitarian responses and promote inclusive governance processes.
hdl:1814/94181
Keywords: 300; Refugee-led organisations; migration governance; forced displacement; humanitarian governance; civil society